Precontact Use of Balsam Fir (Abies balsamea) in Iowa, USA - Green, William; Parker, Kathryn E. (Ethnobiology Letters, 2025)
Excavation of a cave in eastern Iowa (USA) revealed a feature containing charred wood of balsam fir (Abies balsamea) dating to ca. AD 300–400. Taxon identification was based on wood anatomy and species distribution. Balsam fir, a boreal forest species, does not currently grow near the cave but is restricted in Iowa to paleorefugia at algific talus slopes. Balsam fir’s widespread medicinal and ceremonial use, along with the common ritual uses of caves throughout eastern and central North America, suggest the cave might have been the locus of a sweat bath, analogous to sweat lodges used for healing and purification.